Socialization of education and agriculture as a form of active contribution to support the development of independent village communities - Adi Nugraha; Achmad Hafizh (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Lack of awareness and knowledge of the importance of education causes a decrease in student motivation and enthusiasm for studying and achieving dreams, so there is a need for educational socialization and a teaching program in schools and places to recite for students. In addition, there has been no innovation in agriculture, especially related to food security, and household waste is still often disposed of arbitrarily. The purpose of this study is to carry out community service by conducting socialization in the fields of education, agriculture, and waste management, which are still scattered. This program runs for one month, starting with observing the community, then formulating socialization materials and implementing the program directly. This research program went smoothly; it can be seen that the community is enthusiastic about participating in socialization and has begun to make some changes in the way garbage is cleaned. So that little by little, waste can begin to be minimized at certain points. Kesadaran dan pengetahuan yang minim akan pentingnya pendidikan menyebabkan menurunnya motivasi dan semangat siswa dalam menuntut ilmu dan meraih mimpi, sehingga diperlukan adanya sosialisasi pendidikan dan sebuah program mengajar di sekolah dan tempat mengaji bagi para pelajar. Selain itu, belum adanya inovasi di bidang pertanian khususnya terkait ketahanan pangan, dan masih sering membuang sampah rumah tangga seenaknya. Tujuan dari penelitian ini adalah untuk melaksanakan pengabdian masyarakat dengan melakukan sosialisasi dalam bidang pendidikan, pertanian dan penanggulangan sampah yang masih berserakan. Program ini berjalan dalam waktu satu bulan yang dimulai dengan melakukan observasi kepada masyarakat, kemudian merumuskan bahan sosialisasi dan melaksanakan program secara langsung. Program penelitian ini berjalan lancar yang dapat dilihat bahwa masyarakat semangat dalam mengikuti sosialisasi dan mulai melakukan beberapa perubahan dalam cara membersihkan sampah. Sehingga sedikit demi sedikit sampah mulai dapat diminimalisir pada titik-titik tertentu.